Caracterização da pele com estrias Albas, in vivo, com ultrassom de alta resolução e rlastografia supersonic shear imaging - Carvalho, Cátia Pinto (2019)
The High resolution ultrasound (HRUS) and supersonic shear imaging (SSI) elastography are non-invasive, non-ionizing, and easy-to-use methods for analysis of the skin . However, researches are rare using the methods for the study of skin with dermal striae (DS). The study proposed the use of the USAR to identify in vivo dermal lesions (DL) due to the presence of DS and to measure the thicknesses of the skin without and with DS using 2D images and the use of SSI to measure and compare values of Young’s modulus (E) on the skin without and with DS. The work comprised two stages. In phase I, skin 2D images without and with DS of ten volunteers were used to measure and compare their thicknesses. In phase II, skin elastography images without and with DS of the eleven volunteers were used to obtain E values at 0 °, 45 °, 90 °and 315 ° to the skin tension lines (STL). DL caused for DS appeared in 2D images as poor echo areas. A statistically significant reduction in dermis thickness was found (value-p<0.05) in the presence of DS. The mean E values for LTPs were higher in normal skin at 45°(57,72±26,49 kPa) and 90°(55,40±12,04 kPa) and for DS were also at 45° (40,15±12,26 kPa) and 90° (38,33±14,36 kPa). HRUS and SSI have been shown to be promising techniques in the study of the skin with DS and for non-invasive evaluating therapeutic protocols for DS treatment